PWE-023 Is It Worth Chasing Incidental Colonic Hot Spots On Routine Pet Ct Scans?. (9th June 2014) - Ngu, WS; Sinha, R; Aitken, D; Ramadas, A; Reddy, A; Jha, M
Abstract : Introduction: Positron emission tomography (PET) measures metabolic changes at a cellular level enabling detection of early stage disease. Incidental 2-deoxy-[ 18F F]fluoro-2-D-glucose (FDG) colonic uptake is detected in 1.3–3% of patients with up to a third resulting in false positive results. 1 Follow-up endoscopy is recommended to further distinguish these FDG avid lesions. 2 Cancer detection rates of 7.8–18.9% have been quoted in various studies. 1, 3 Our aim was to evaluate colonic FDG avid lesions on PET by endoscopy. Methods: An analysis of prospectively collected database of all patients (n = 1564) who had PET for various malignancy between January 2011 to September 2013 was performed. Results: Fifty-nine (3.77%) patients had focal colonic FDG uptake and 45 (2.87%) patients went on to have colonoscopy. Indications for PET CT for those undergoing endoscopy was lung carcinoma (22), gastrointestinal carcinoma (10), laryngeal carcinoma (7) and lymphoma (6). Median age was 64 with a male preponderance (2.5:1) Location on PET CT was categorised to sigmoid (23), rectal (9), anorectal (4), caecal (3), hepatic flexure (2), transverse (1), splenic flexure (1), ascending (1) and descending (1). Findings on endoscopy ranged from polyps (22), normal (9), diverticulosis (8), sigmoid cancer (4), caecal cancer (1) and colitis (1). In total, out of the all patients who had endoscopy, 20 (44.4%) were found to have low grade tubullovillous adenomas, 5 (11.1%) had cancer, whilst 2 (4.4%) had hyperplastic polyps on histology. Conclusion: These findings are in keeping with other series and suggest that it makes sense only to carry on with current practice of following up these hot spots with endoscopy. References: 1 Israel O, Yefremov N, Bar-Shalom R, Kagana O, Frenkel A, Keidar Z, et al . PET/CT detection of unexpected gastrointestinal foci of 18F-FDG uptake: incidence, localization patterns, and clinical significance. J Nucl Med 2 005;46:758–762 2 Tatlidil R, Jadvar H, Bading JR, Conti PS. Incidental colonic fluorodeoxyglucose uptake: correlation with colonoscopic and histopathologic findings. Radiology 2002;224:783–787 3 Putora PM, Muller J, Borovicka J, Plasswilm L, Schmidt F. Relevance of incidental colorectal FDG-PET/CT-enhanced lesions. Onkologie 2013;36(4):200–4 Disclosure of Interest: None Declared.